Application of the Promethee II Method for Determining Road Improvement Priorities - Mayang Sari; Kosim Kosim; Andika Saputra (MASI Mandiri Edukasi, 2023)
The road is an infrastructure that is often passed by the community. If there is damage, it will significantly disrupt community activities; for example, road conditions become jammed. This is necessary for the Public Works and Spatial Planning Office of the City of Cirebon to handle the road repairs, but in carrying out repair planning, there are obstacles, one of which is the difficulty in determining priority for road repairs with limited funds from the center. This research decision support system using the Promethee II method aims to find accurate results that are useful in determining priority road repairs that will be selected for repair. The criteria used in this study are Section Length, Road Width, Damage Condition, Traffic Volume (LHR), and Road Access. The results of this study selected Jalan A1 as an alternative that had the highest rating level of 0.613333333, and this indicated that this road was a road that had to be prioritized for repair. The test results show that the Promethee II method can produce priority recommendations for road improvements based on the required criteria.